Strategy of Development of Socially Oriented Business Environment of Lviv - Melnyk, M.I. (Економічний вісник Донбасу, 2013)
In the article strategic priorities and recommendations concerning formation and development of sociallyoriented business-environment are substantiated; author’s concept on formation of a socially-oriented businessenvironment is offered, which is based on the definition of its system characteristics, levels, principles, criteria, prerequisites. The development strategy of sociallyoriented business environment contains organizational and economic instruments promoting social responsibility and solidarity of business, government and society, and enhance the prestige of institutionalization of socially responsible standards of behavior of economic agents. У статті обґрунтовано стратегічні пріоритети та рекомендації щодо формування і розвитку соціально орієнтованого бізнес-середовища; запропонована авторська концепція формування соціально орієнтованого бізнес-середовища, яка базується на визначенні його системних характеристик, рівнів, принципів, критеріїв, передумов розвитку. Стратегія розвитку соціально орієнтованого бізнес-середовища містить організаційно-економічні інструменти стимулювання соціальної відповідальності та згуртованості бізнесу, держави і суспільства, підвищення престижу й інституціалізації соціально відповідальної культури поведінки економічних суб'єктів. В статье ообоснованы стратегические приоритеты и рекомендации формирования и развития бизнес- среды; предложена авторская концепция формирования социально ориентированнойбизнес-среды, базирующаяся на определении его системных характеристик, основных уровней, принципов, критериев, предпосылок развития. Стратегия развития социально ориентированной бизнес-среды содержит организационно-экономические инструменты стимулирования социальной ответственности и сплоченности бизнеса, государства и общества, повышения престижа и институционализации социально ответственной культуры поведения экономических субъектов.